Mobilitas Tenaga Kerja Indonesia Ke Luar Negeri Dan Dampaknya Terhadap Diri Migran Suatu Tinjauan Awal Terhadap Kasus Buruh Bangunan Di Kuala Lumpur - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
ABSTRAK This writing is the outcome of studies concerning Indonesian migrant in the construction sector in Kuala Lumpur. Although in the beginning of this paper, there are many explanation about the development condition of Indonesian international labour with the purpose to picture the global trend since the first five year development plan until the sixth five year development plan, but the focus in this writing is more on the impact analysis for the migrant oneself in the destination country. The result of the studies shows that the migrant income level increase in proportion to when living in Indonesia especially in fulfilling the basic requirements. On the contrary, for job experience many says that they have no progress at all and in fact rather become stupid. The migrants also infected with various diseases especially skin diseases and back ache. Likewise sexual behaviour, there is a tendency to have sexual intercourse with the fellow migrant or go to the cheap prostitution places around Kuala Lumpur.